Ejection fraction and NYHA class in heart failure in the REGENERATE–IHD stem cell study: a comparison between the intramyocardial and intracoronary arms. (22nd September 2015) - Yeo, C; Locca, D; Wong, J; Saunders, N; Preston, M; Brookman, P; Archbold, A; Rothman, M; Mills, P; Agrawal, S; Mathur, A
Abstract : Introduction: The ongoing REGENERATE–IHD study is a randomised controlled trial designed to test the safety and efficacy of bone marrow-derived progenitor cells as therapy for heart failure. It compares three different methods of cell delivery: intramyocardial, intracoronary and peripheral mobilisation using granulocyte–colony-stimulating factor (G–CSF). Placebo controls are included in each arm and the specific treatment assignment will only be revealed at the end of the trial. We have evaluated changes in left ventricular ejection fraction (LVEF) and NYHA class in the first 29 patients randomly assigned to the intramyocardial versus intracoronary arms of the study. Methods: Patients with NYHA class II–IV heart failure secondary to ischaemic heart disease, on optimal medical treatment with no further treatment options, were randomly assigned in the REGENERATE–IHD study (14 in the intramyocardial arm, 15 in the intracoronary arm). LVEF changes were assessed with left ventricular angiography and clinical outcome with NYHA classification at baseline and at 6 months. At present, the study authors remain blinded to progenitor cells or placebo allocation within each arm. Results: At baseline, mean LVEF between the two treatment arms was not significantly different (p = 0.62, unpaired t test). Between baseline and 6 months, LVEF did not alter significantly from 43.63% ± 17.03% to 43.02% ± 14.57% (p = 0.78) within the intramyocardial arm, and from 40.98% ± 10.94% to 38.95% ± 11.33% (p = 0.27) within the intracoronary arm (fig ). No significant difference in LVEF change was seen between the two treatment arms. Similarly, at baseline there was no significant difference in the NYHA class between the two treatment arms (p = 0.50, Mann–Whitney test). At 6 months, the NYHA class improved significantly from 2.71 ± 0.61 to 2.14 ± 0.53 (p = 0.0057) in the intramyocardial arm. A similar trend towards NYHA class improvement from 2.53 ± 0.52 to 2.33 ± 0.72 (p = 0.1887) was seen in the intracoronary arm. Conclusions: Contrary to the predicted decline in LVEF usually associated with such a high-risk cohort, cardiac function was preserved in patients within both the intramyocardial and intracoronary treatment arms over a 6-month period. Although we remain blinded to treatment assignment within each arm, we speculate that the overall preservation of LVEF in this early analysis might be related to progenitor cell therapy. There was a significant improvement in NYHA functional class noted in patients in the intramyocardial group. However, an attendant change in cardiac function was not apparent at this stage. These results suggest that preservation of cardiac function may be a tenable goal of such biological therapy.